Modafinil Administration to Preadolescent Rat Impairs Non‐Selective Attention, Frontal Cortex d2 Expression and Mesolimbic Gaba Levels - Renard, G; Cid-Jofre, V (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The misuse of psychostimulants is an increasing behavior among young people, high-lighting in some countries the abuse of modafinil (MOD) as a neuropotentiator. However, several clinical trials are investigating MOD as an alternative pharmacological treatment for attentional deficit and hyperactivity disorder (ADHD) in children and adolescents. On the other hand, the early use of psychostimulants and the misdiagnosis rates in ADHD make it crucial to investigate the brain effects of this type of drug in young healthy individuals. The aim of this work was to evaluate the effects of chronic MOD treatment on neurochemicals (γ‐aminobutyric acid and glutamate), dopa-mine receptor 2 (D2) expression and behavior (non‐selective attention “NSA”) in the mesocortico-limbic system of young healthy Sprague–Dawley rats. Preadolescent male rats were injected with MOD (75 mg/kg, i.p.) or a vehicle for 14 days (from postnatal day 22 to 35). At postnatal day 36, we measured the GLU and GABA contents and their extracellular levels in the nucleus accumbens (NAc). In addition, the GLU and GABA contents were measured in the ventral tegmental area (VTA) and D2 protein levels in the prefrontal cortex (PFC). Chronic use of MOD during adolescence induces behavioral and neurochemical changes associated with the mesocorticolimbic system, such as a reduction in PFC D2 expression, VTA GABA levels and NSA. These results contribute to the understanding of the neurological effects of chronic MOD use on a young healthy brain. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.